(untitled) (Research, Society and Development, 2021)
Cancer is the name given to a set of complex diseases characterized by the uncontrolled growth of abnormal cells with a high invasive potential, being considered one of the biggest public health problems in the world. The incidence of cancer has increased every year, showing the relevance of conducting research aimed at treating cancer in its various modalities. Thus, this work aims to carry out a scientific and technological prospection on the application of nanoparticles with sodium alendronate in the treatment of cancer. For this, the following keywords were used, with the Boolean operator AND, in the searches: “Sodium alendronate and nanoparticle”, “Sodium alendronate and cancer”, “Nanoparticle and cancer”. The results demonstrated in scientific prospecting a large amount of work related to cancer when associated with nanoparticles. It was found that in the last 10 years there has been a linear growth in scientific production focused on this topic. The same was observed in the search for patents, where up to 37,100 patent applications were observed with these terms in their structure, in the Espace Net database. with nanotechnology a viable and promising alternative.